Biliary excretion and enterohepatic circulation of thienorphine and its glucuronide conjugate in rats - Jingting Deng; Xiaomei Zhuang; Guolin Shen; Hua Li; Zehui Gong (Elsevier, 2012)
Thienorphine (TNP) is a new partial opioid agonist currently developed as a promising drug candidate with the intended clinical indication for the treatment of opioid dependence. The pharmacokinetic profile and biliary excretion of TNP and its glucuronide conjugate (TNP-Glu) were investigated after oral administration of TNP in rats. The concentrations of TNP and TNP-Glu were simultaneously quantified using a LC-MS/MS method. A double peak phenomenon was observed in TNP plasma concentration-time curves with the secondary peak appeared at 6-8 h. A slower decline of plasma concentrations in the terminal phase was observed for TNP with T1/2 of 7.01 h. TNP-Glu was the predominant component in rat plasma and bile. Its plasma level was about 10 times higher than TNP and the 24 h accumulative bile excretion rate was 23%. Enterohepatic circulation of TNP and TNP-Glu was evaluated using a paired rat model. In bile-donor rats, no double-peak was detected and the elimination half life of TNP was significantly shortened (3.71 h) when compared to intact rats (7.01 h, P<0.05). Both TNP and TNP-Glu were detected in bile-recipient rats. Their exposures in recipient rats due to enterohepatic circulation were 15.6% and 42.6% for the parent drug and the metabolite, respectively. The deconjugation of the glucuronide conjugate and the reabsorption of free TNP were further confirmed in in situ perfused rat intestinal preparations. These results indicate that the enterohepatic circulation has a significant influence on the systemic exposure of the parent drug and its glucuronide conjugate, particularly on the terminal elimination of TNP, which may result in the prolonged retention of the drug in body.